Analysis of the Need for Electronic Module IPAS Development to Improve Independence, Creativity and Critical Thinking - Aristawati, Ika Vidiasari; Marwoto, Putut; Ellianawati, Ellianawati (Physics Communication, 2023)
According to the HDI, science education in Indonesia has a low number in producing students with independence, creativity, and critical thinking. In fulfilling and improving these criteria, the use of media learning based on Android, HTML, and offline-accessible applications has been enforced. The purpose of this research is to examine the need for developing learning media aiming to increase students' independence, creativity, and critical thinking. Descriptive narrative survey research is used as the method to employ the instrument indicators, including independence, creativity, and critical thinking. The instrument indicators consist of learning process, the need for electronic materials and supporting facilities and infrastructure. This study was conducted on 40 teachers, 3 male and 37 female, at SMK Pusat Keunggulan and 125 students, two females and 123 males, at SMKN 1 Trenggalek, two female and 123 male students. The survey on the students is also conducted to acknowledge and measure the indicators, including independence, creativity, and critical thinking. Data analysis is carried out through the validation of the instrument as the first step. After being revised, the implementation of the instrument was then conducted. Following the steps, the data were analyzed by applying Likert analysis. Based on the data obtained, 88% of the students and 100% of the teachers required innovative, intriguing, and accessible electronic-based materials to support and enhance both comprehensions of the lessons. Students who are categorized as less independent have 83.25% independency, 68.25%, and 83% critical thinking in average. As a result, learning media that are accessible offline, based on Android, HTML, and applications, are required.